Simulation of experimental chronic osteomyelitis - Svyatoslav B. Korolev; Natalya Yu. Orlinskaya; Vyacheslav N. Mitrofanov; Oleg P. Zhivtsov; Daria P. Yulina (Гений oртопедии, 2022)
data from Introduction There is no unified scheme for creating a pathological site in the existing osteomyelitis models. The location, the size of the defect, the dosage of the infecting agent and the carrier material are to be standardized to facilitate reliable comparative data from different authors and reproducibility of the experimental model. The objective was to demonstrate experimental results of simulated chronic osteomyelitis using a unified scheme for creating a pathological site. Material and methods An identical defect was simulated in the proximal tibia metaepiphysis of 15 rabbits using a four-sided cone-shaped drill with a diameter of 0.5 cm and a limiter to a depth of 0.5 cm. An allobone fragment impregnated with Staphylococcus aureus suspension with a microbial cell concentration of 1.0 × 108 CFU/mL was placed into the defect site. A part of sutures was removed from the middle third of the wound and the edges were diluted to initiate a fistula course at 3 postoperative days. An experimental model of chronic osteomyelitis was developed using unified parameters of location, defect size, dosage of the infecting agent and carrier material. The method was technically simple, required no additional infection and provided a chronic osteomyelitic process. Observation period was 21 days. The control of the model formation was produced through clinical observation, inflammatory changes in the peripheral blood, bacteriological, radiological and pathomorphological examinations. Results Postoperatively, the animals demonstrated a decreased physical activity, increased body temperature, impaired function of the operated limb, a non-healing fistula with an abundant purulent discharge of curd consistency formed at the site of the postoperative wound. Computed tomography showed a cavity with irregular sclerotic edges filled with multiple bone sequesters, edema of adjacent soft tissues and fistula at 21 postoperative days. Leukocytosis was observed in the peripheral blood. Bacteriological examination of the wound discharge showed growth of Staphylococcus aureus. Pathomorphological investigation indicated chronic osteomyelitis with bone defects in the proximal metaepiphysis of the tibia and necrotic areas, pronounced leukocyte infiltration, fragments of dissolving bone tissue, growth of connective tissue surrounding foci of chronic purulent inflammation. An experimental model of chronic osteomyelitis was developed using unified location parameters, defect size, dosing of the infecting agent and carrier material. The method was technically simple, required no additional infection and facilitated formation of a chronic osteomyelitic process for 21 days. Discussion We used allobone in our model to cause infection by impregnation of microbial suspension without additional removal of the carrier. The amount of infecting suspension to initiate osteomyelitic process to be absorbed by the allobone and avoid the death of the animal from septic complications was determined in the course of the study. For passive drainage of the wound, a fistula course was provided and its functioning maintained, with the osteomyelitic focus localized and survival of animals ensured throughout the experiment. Conclusions An experimental model of chronic osteomyelitis was demonstrated using a unified scheme for a pathological focus. The model allowed us to avoid generalization of the osteomyelitic process, ensure the survival of animals throughout the experiment and simulate the process being consistent with pathomorphological changes characteristic of human chronic osteomyelitis.